The Effect of Self-Efficacy and Self-Esteem on Academic Achievement of Grade 10 Students at MAN Kota Palangkaraya - Fahrurrazi Fahrurrazi; Asep Solikin; Agung Riadin (International Journal of Universal Education, 2026)
Academic performance among adolescents in Palangkaraya City is influenced by various internal factors, specifically the psychological constructs of self-efficacy and self-esteem. This study aims to investigate the relationship between self-efficacy, self-esteem, and the academic achievement of students. The research utilizes a quantitative approach with a correlational study design. The sample consists of 183 students from MAN Palangkaraya, selected to represent the student population in the region. Data were collected using Indonesian-adapted versions of the Academy Self-efficacy Scale and the Self-esteem Inventory – Long Form (SEI-LR). To ensure the instruments' cultural and linguistic suitability, a pilot study was conducted to establish reliability and validity within the local context. A Pearson correlation analysis will be conducted to evaluate the linear relationship between these variables. It is hoped that the findings will contribute to a deeper understanding of how self-efficacy and self-esteem impact academic success. The results are intended to provide a guide for developing educational strategies focused on enhancing these psychological traits to improve overall student academic achievements.